Influence factors to flood disaster and search and rescue capacity in Thua Thien Hue delta - An, Pham Thanh; Bac, Dao Dinh; Xuan, Nhu Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 3, 2012)
Abstract: